Clinical Diabetes and Endocrinology - Tan, Meng
Clinical Diabetes and Endocrinology is an open access journal publishing within the field of diabetes and endocrine disease. The journal aims to provide a widely available resource for people working within the field of diabetes and endocrinology, in order to improve the care of people affected by these conditions. The audience includes, but is not limited to, physicians, researchers, nurses, nutritionists, pharmacists, podiatrists, psychologists, epidemiologists, exercise physiologists and health care researchers. Research articles include patient-based research (clinical trials, clinical studies, and others), translational research (translation of basic science to clinical practice, translation of clinical practice to policy and others), as well as epidemiology and health care research. Clinical articles include case reports, case seminars, consensus statements, clinical practice guidelines and evidence-based medicine. Only articles considered to contribute new knowledge to the field will be considered for publication.